2016
DOI: 10.4103/1735-9066.180392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peer education on the noise management in Iranian neonatal intensive care unit

Abstract: Background:Advancements in neonatal intensive care unit (NICU) science and technology have increased the survival rate of preterm infants. Despite these advances, they are still facing with neurobehavioral problems. Noise level in NICU is a potential source of stress for preterm infants. It should be decreased to the standard level as much as possible. The purpose of this study was to evaluate the effect of peer education on the performance of staff in noise management in the NICU.Materials and Methods:A pre-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Other research highlights the importance of behavior modification, such as teaching healthcare teams about noise and sensitization to noise sources. For example, Biabanakigoortani et al 28 found peer education of staff in the NICU decreased unnecessary noise generated by the staff. These results are consistent with our findings: One of our participants suggested the importance of peer education and creating a sense of responsibility in all staff.…”
Section: Discussionmentioning
confidence: 99%
“…Other research highlights the importance of behavior modification, such as teaching healthcare teams about noise and sensitization to noise sources. For example, Biabanakigoortani et al 28 found peer education of staff in the NICU decreased unnecessary noise generated by the staff. These results are consistent with our findings: One of our participants suggested the importance of peer education and creating a sense of responsibility in all staff.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on peer group education in various diseases,[89] although a few have focused on diabetes care, especially in the elderly. One study on the effect of peer group education in patients with diabetes found that blood glucose levels improved in patients supported by peer groups compared to the group which only received insulin injection.…”
Section: Introductionmentioning
confidence: 99%
“…21 Also, the results of another study by Safaei et al on the effects of a peer group educational program in promoting self-care in TM patients indicated improvement in self-care behaviors in the intervention group compared to the control group up to four months after the intervention. 19 Also, Giese-Davis et al in their study on the quality of life of patients with breast cancer showed that peer education improved the quality of life of these patients up to one year after diagnosis. 27 In a study on diabetic patients, Heisler et al showed that a peer-support program promoted self-care behaviors and proper use of drugs and decreased insulin requirements in the intervention group compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…This type of education improves individuals' knowledge, attitude and practice. 19 Peer groups can more effectively encourage their counterparts to adhere to appropriate health behaviors and share their strengths, weaknesses, and experiences. 20 The members of peer groups can also better communicate with their peers and help them behave better.…”
Section: Introductionmentioning
confidence: 99%